Business Performance of Batik Traders in Semarang According to Javanese Islamic Trade Culture - Daryono Daryono; Adijati Utaminingsih; Witjaksono E.H. (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This study seeks to analyze the business performance of batik traders in the Johar Baru market of Semarang City, focusing on Javanese Islamic trade culture as an integral aspect of Javanese culture. This culture is characterized by three essential traits: harmonious, functional structural, and transcendental. The application of these characteristics draws from local wisdom rather than directly from the Qur'an or Hadith; however, upon closer examination, they do not contradict Islamic teachings. Thus, the business performance of batik traders in Johar market effectively reflects Javanese Islamic ethical values in trade. Employing qualitative research methods with a single case study design, the analysis followed the framework proposed by Miles and Huberman, which encompasses data reduction, data presentation, and conclusion drawing/verification. Informants were selected through purposive sampling techniques, which included in-depth interviews, documentation review, and focus group discussions. The study revealed that the moral attitudes and business performance ethos of batik traders in the Johar market are grounded in these three characteristics of Javanese cultural moral values: harmonious, functional structural, and transcendental. The identification of their performance is illustrated through various concepts that form several propositions. These findings culminated in the development of a new mini-theory termed the